Los proyectos económicos del Congreso de Michoacán, 1825-1848 - Ballesteros Vega, Marco Vinicio (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
In this research we discourse about the way the local Legislature discussed the economic agricultural, mining and manufacturing projects of the period 1825-1848. in terms of economic development in order to elaborate the economic policy for the State of Michoacan. Under the premise that the elaboration of economic policy is carried out jointly with the institutional construction of the State and taking into account our close relationship with Western culture, we address the problem in question in the following manner: In the first chapter we address the political-philosophical discussion of the seventeenth and nineteenth centuries over the construction of the state, civil society, laws and institutions that guarantee the rights and representation of the individual. Later, we review the mercantilist, physiocratic, political economy and utilitarian economic doctrines discussed in the same period, as well as their diverse conceptions about the production of wealth. This allows us to understand the ideas discussed, as well as the way to build promotion proposals in the West. The second chapter exposes the construction of the State of Michoacan, based on the search for political representation of the provincial spaces and the various proposals regarding the Federalization of Mexico. Later we point out the importance of the Legislature in the definition of the State, the construction of the order of government, laws and local institutions. Finally, in the third chapter the discussions, proposals and debates held in the Legislative Hall are tackled. In agricultural matters: on the fractionation of communal property, colonization of wastelands, the mechanisms designed to occupy the population for productive purposes and the fiscal incentives of the sector. For mining: the encouragement of private investment, the colonization of land for the exploration of new deposits, as well as the fiscal incentives of the sector. Finally, for the manufacturing stimulus: infrastructure and communications projects, measures to prosecute smuggling, fiscal incentives and stimulation of the local textile industry. With all this, we discourse over the discussion held in Congress about the projects, the ideas used and their relationship with the economic doctrines referred to understand what they conceived as wealth generating activities.

Con el presente trabajo de investigación disertamos sobre la forma en que se discutió en el Legislativo local en términos de fomento económico para elaborar la política económica del Estado de Michoacán en torno a los proyectos económicos agrícolas, mineros y manufactureros del periodo 1825-1848. Bajo la premisa de que la elaboración de la política económica se realiza de manera conjunta a la construcción institucional del Estado y tomando en cuenta nuestra relación estrecha con la cultura occidental abordamos la problemática en cuestión de la siguiente manera: En el primer capítulo abordamos la discusión político-filosófica de los siglos XVIIXIX en torno a la construcción del Estado, la sociedad civil, las leyes e instituciones que garantizan los derechos y la representación del individuo. Posteriormente hacemos un recorrido por las doctrinas económicas mercantilista, fisiócrata, economía política y utilitarista discutidas en el mismo periodo, así como sus diversas concepciones sobre la producción de riqueza. Lo cual nos permite entender las ideas discutidas, así como la forma de construir las propuestas de fomento en Occidente. El segundo capítulo trata sobre la construcción del Estado de Michoacán, a partir de la búsqueda de representación política de los espacios provinciales y las diversas propuestas en torno a la Federalización de México. Posteriormente observamos la importancia del Legislativo en la definición del Estado, la construcción del orden de gobierno, leyes e instituciones locales. Finalmente, en el tercer capítulo se abordaron las discusiones, propuestas y debates realizados en el recinto Legislativo. En materia agrícola: sobre el fraccionamiento de la propiedad comunal, colonización de baldíos, los mecanismos diseñados para ocupar a la población con fines productivos y los incentivos fiscales del rubro. En cuanto a la minería: el estímulo de la inversión privada, la colonización de tierras para la exploración de nuevos yacimientos, así como los incentivos fiscales del sector. Finalmente, para el estímulo manufacturero: los proyectos de infraestructura y comunicaciones, las medidas de persecución del contrabando, los incentivos fiscales y el estímulo del ramo textil local. Con todo esto observaremos la discusión realizada en el Congreso en torno de los proyectos, las ideas utilizadas y su relación con las doctrinas económicas referidas para entender lo que conciben como actividades generadoras de riqueza.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2018-0045; Opción en historia regional continental; Poder legislativo; Sistemas de gobierno representativos; Riqueza nacional; Fomento económico; Propiedad privada; Agricultura; Minería; Comercio; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/305